Rubric as a learning tool in teaching application of derivatives in basic calculus - Leah Conejos Auxtero; Roar Abalos Callaman (Department of Mathematics Education, Universitas Muhammadiyah Surakarta, 2021)
Rubric has been associated with the term assessment used for grading and/or scoring. However, it might observe less, but it is also designed as students ‘learning tool. This study was conducted to provide empirical facts on its effectiveness as a learning tool in teaching Applications of Derivatives in Basic Calculus. It used the quasi-experimental design called the pretest posttest design. The participants were the 96 students from two classes of Grade 11 STEM students at the University of Mindanao. The instruments used were the adapted and improved rubric designed from two different research, a 25-item teacher-made problem-solving test questionnaire that was used in both pretest and posttest to measure the performance of the experimental and control group. The test questionnaire and rubric were both validated by 3 experts in the field with a result of very good, and it has a good internal consistency. The data gathered were summarized, translated, and analyzed using the mean scores of pretest and posttest. Findings showed that both the experimental and control group showed improvement, however, the experimental group who used rubric as a learning tool showed more significant improvement than control group. Thus, using a rubric as a learning tool in teaching Applications of derivatives is effective in improving students’ academic achievement as it teaches students to develop their understanding of procedural knowledge.